Sri Lanka's drone pioneers - Siddiqui, Salman (Technical Centre for Agricultural and Rural Cooperation, 2016)
The International Water Management Institute in Sri Lanka has begun to experiment with drone technology to support a wide range of studies like crop monitoring, disaster mitigation and disease prevention.